The Effects of Surfactant on Oxygenation in Term Infants with Respiratory Failure - Beken, Serdar (Tehran University of Medical Sciences, 2013)
OBJECTIVE: The objective of the study was to evaluate the effects of exogenous surfactant on respiratory indices in term infants with respiratory failure. METHODS: Consecutive 18 mechanically ventilated term infants, who received a single dose of exogenous surfactant were retrospectively included into the study. The respiratory outcome of surfactant rescue therapy was evaluated by comparing respiratory indices before and six hours after surfactant administration. FINDINGS: Median oxygenation index (OI), mean alveolar pressure (MAP) and fraction of inspired oxygen (FiO(2)) values were significantly decreased (P<0.001); median arterial oxygen partial pressure (PaO(2)), arterial oxygen saturation (SaO(2)) and PaO(2)/FiO(2) values were significantly increased six hours after surfactant treatment (P<0.001). CONCLUSION: Rescue therapy with surfactant was found to be effective in the improvement of early respiratory indices in term infants with respiratory failure.